A mediação do professor em processos de pesquisa escolar na Web: estratégias para o desenvolvimento do letramento digital - Roberta Garcia (2021)
This study aimed to reveal the importance of the role of the teacher in the systematized mediation of school research on the Web for students from Elementary School II. This research assumes that students at this school stage, when doing research, do not have the skills that allow them to use strategies to search for, read, and evaluate sources, nor do they have the ability to select and integrate information they come across on the Internet. For this reason, when doing school research, they merely perform the simple actions of copying and pasting the texts exactly as they find them, only for the purpose of teacher assessment. On the other hand, teachers do not have the habit of proposing a more reflective and critical teaching when it comes to school research, and often reinforce an obsolete practice that does not help to expand the literacies of students. Thus, this investigation is justified by presenting a teaching proposal that came to add specific knowledge to a school research process, in a digital environment, aimed at expanding the digital literacy of participating students. To this end, this work was based on theoretical concepts about school research conception (MARTINS, 2001; BAGNO, 2005; DEMO, 2006, GIL, 2010; FREIRE, 1996; MILANESI, 1983); teaching school research on the Web (MORAN, 1997/2012; MASETTO, 2000; PRENSKY, 2001; MARKET, 2002; KENSKI, 2008; XAVIER, 2008; WILEY et al., 2009; CANI, 2019); digital literacy (GILSTER, 1997; ESHET-ALKALAI, 2004; BADWEN, 2008; JONES AND HAFNER (2012); procedures, competencies, and school research skills (MARTINS, 2001; DAYS AND NOVAIS, 2009; KINGLEY AND TANCOCK, 2013; EISENBERG AND BERKOWITZ, 2018); and, finally, teacher mediation (WOOD, BRUNER AND ROSS, 1976; VYGOTSKY, 1991/2001; LÉVY, 1999; FREIRE, 1987; LEBANON, 2004; KLEIMAN, 2006/2007). The methodology of this research was configured as an action research, of qualitative nature, in addition to quantitative analysis of some data. The action research was implemented in a school in Brumadinho/MG, through a teaching project, with 83 students from 8th and 9th grade classes. The project was elaborated with six workshops that addressed the themes to be researched; the web research process, conducted spontaneously by the students; and the teaching/mediation of the most appropriate procedures to carry out the study in a more conscientious manner, especially as regards the assessment of sources and texts found on the Web. Data generation methods included questionnaires, participatory observation video recordings, screen capture, and reports in multimodal learning journals. The data were analyzed through a specific digital literacy matrix for web research, elaborated by the researcher herself, and based on the resumption of the theoretical contribution that served as the foundation for this research. The results indicated that the students showed difficulties when doing school research alone, especially with web support. On the other hand, this same process, mediated by the teacher, allowed the students to understand the functioning of some tools, and to locate, assess, and produce information in a more critical, reflexive, and ethical manner, seeking solutions to their constant questions and playing a role in their learning. Moreover, since the daily life of students is largely mediated by technological devices, teaching through such devices has incited greater interest and, consequently, more active participation in research. Thus, it is possible to argue that teacher mediation is essential in order to develop self-confidence, autonomy, and social transformation.